2008
DOI: 10.1149/1.2969277
|View full text |Cite
|
Sign up to set email alerts
|

FESEM and EIS Study of Sealed AA2024 T3 Anodized in Sulfuric Acid Electrolytes: Influence of Tartaric Acid

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in: http://oatao.univ-toulouse.fr/ Eprints ID : 2407To link to this article : URL : http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
93
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 40 publications
11
93
0
7
Order By: Relevance
“…[4][5][6] The restriction on the use of chromium Cr (IV) compounds has also led to the development of alternative chromium-free anodizing methods, including the sulfuric-tartaric process (TSA), a typical anodizing method used in aerospace industries. [7][8][9][10] In simple terms, the anodizing process is used to obtain a thick aluminum oxide layer with a porous structure, whereas the sealing process is used to close the pores with hydrated products, thereby further increasing the corrosion resistance. A detailed discussion of the complex effects of pore morphology, film thickness, sealing time and nature of the sealing solution can be found elsewhere and it is not reported in detail here.…”
mentioning
confidence: 99%
“…[4][5][6] The restriction on the use of chromium Cr (IV) compounds has also led to the development of alternative chromium-free anodizing methods, including the sulfuric-tartaric process (TSA), a typical anodizing method used in aerospace industries. [7][8][9][10] In simple terms, the anodizing process is used to obtain a thick aluminum oxide layer with a porous structure, whereas the sealing process is used to close the pores with hydrated products, thereby further increasing the corrosion resistance. A detailed discussion of the complex effects of pore morphology, film thickness, sealing time and nature of the sealing solution can be found elsewhere and it is not reported in detail here.…”
mentioning
confidence: 99%
“…It was concluded that the presence of tartaric acid results in the formation of anodic films with lower porosity than those produced by DSA anodizing. The EIS study revealed that corrosion resistance of sealed anodize film in TSA is significantly better than the sealed film obtained by DSA anodizing which is mainly associated with the higher compactness of the porous layer and higher resistance of the hydrothermallysealed barrier layer [6].…”
Section: Introductionmentioning
confidence: 90%
“…Anodizing in dilute sulphuric acid (DSA) is performed to obtain thin anodize layer (1 -5 µm) that gives lower impact on the fatigue strength of the alloy. However, despite an improvement of fatigue strength of the alloy, its corrosion resistance is still lower than the alloy being anodized in CA [6].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…35,37,41 Further, on more complex potential-time cycles, typical of industrial practice and resulting in morphologies that vary across the film thickness, the sealing behavior still requires investigation.…”
Section: C908mentioning
confidence: 99%